Effect of the Lead(II) Bond Angle on the Reactivity of Diaminoplumbylenes toward Ammonia: From Inertness to Immediate Ammonolysis - Guthardt, Robin; Bruhn, Clemens; Färber, Christian; Siemeling, Ulrich (Organometallics, 2020)
The reactivity of the N-heterocyclic plumbylenes o-C6H4(NSiRMe2)(2)Pb (R = M; t-Bu), nap(NSiRMe2)(2)Pb (nap = naphthalene-1,8-diyl; R = Me, t-Bu), and [Fe(eta(5)-C3H4)NSit-BuMe2(2)Pb] as well as of the acyclic diaminoplumbylene [(Me3Si)(2)N](2)Pb toward ammonia depends critically on the N-Pb-N bond angle. The five-membered-ring congeners have the smallest angles (ca. 78 degrees) and are inert toward NH3. The acyclic and the ferrocene-based congeners exhibit the largest Pb-II bond angles (ca. 104 and 99 degrees, respectively) and undergo immediate ammonolysis. The naphthalene-based six-membered-ring congeners have intermediate bond angles (ca. 83 degrees) and show significantly slower ammonolysis, which allowed the isolation of the reactive intermediate [Pb(mu-NH2)nap(NSiMe3)(NHSiMe3)](2) at low temperatures. The plumbylenes of this study which undergo ammonolysis also react readily with aniline.
CRIS-Team WoS Importer:2021-01-15